Recuperação da biomassa de algas de lagoas de estabilização por flotação por ar dissolvido - Torres, Dayana Melo (2017)
This research evaluated the performance of a flotation system for the recovery of the algal biomass of the stabilization pond effluents located in the Brazilian northeast and used for the treatment of domestic sewage. The biomass recovery aims to evaluate its use as a raw material for biodiesel production. Two coagulants, aluminum polychloride (PAC) and ferric chloride (CF), were tested in the different effluent samples following an experimental design in random factorial (3^4-1 - 4 factors and 3 levels), in triplicate. The factorial analysis showed that the coagulant dose was the most important factor in the PAC experiments for facultative and maturation ponds. For PAC, it is possible to work with the pH of the natural sample, dosage of 100 mg/L, recirculation rate of 10% and flocculation time of 15 minutes, being able to recover a seaweed biomass on a dry basis of about 1609 kg/day and 764 kg/day for the facultative and maturation ponds, respectively. The application of CF in FAD was more efficient, and the use of coagulants can be done in smaller amounts, with a concentration of 75 mg/L; however, a pH correction of 5.5 is required, generating a biomass on a dry basis of 1099 kg/day for the facultative pond and 776 kg/day for the maturation pond. The predominant genera in the biomass of the ponds were Synechococcus sp., Synechocytis sp. and Chlorella sp. The extraction of the biomass lipid fraction was done with a mechanical stirrer associated with ultrasound, using n-hexane, the extract being analyzed through spectroscopic and thermogravimetric techniques. The best yield (5.18%), in terms of biomass lipid material, was verified in the samples of the facultative pond with PAC. Infrared spectra and thin layer chromatography detected the presence of ester, fatty acids and triglycerides in the extract of the lipid material, and the atomic absorption analyzes indicated the presence of iron and aluminum contents in the dry and residual biomass. According to the results obtained in this research it is concluded that the lipid material extracted from the microalgae identified in the stabilization pond has the potential to produce an oil rich in triglycerides that can be used in the production of biodiesel.